Compound Heat Transfer Enhancement in Dimpled and Sinusoidal Metal Solar Wall Ducts Fitted with Wired Inserts - Mohammed H. Mahmoud; Fouad A. Saleh; Abeer H. Faleh (Journal of Engineering, 2023)
An improved Metal Solar Wall (MSW) with integrated thermal energy storage is presented in this research. The proposed MSW makes use of two, combined, enhanced heat transfer methods. One of the methods is characterized by filling the tested ducts with a commercially available copper Wired Inserts (WI), while the other one uses dimpled or sinusoidal shaped duct walls instead of plane walls. Ducts having square or semi-circular cross sectional areas are tested in this work. A developed numerical model for simulating the transported thermal energy in MSW is solved by finite difference method. The model is described by system of three governing energy equations. An experimental test rig has been built and six new duct configurations have been fabricated and tested. Air is passed through the six ducts with Reynolds numbers from 1825 to 7300. Six, new, correlations for Nusselt number and friction factor are developed to assess the benefits that are gained from using the WI and the dimpled and sine-wave duct walls. It is found that higher heat transfer rates are achieved using the Dimpled, semi–circular duct with Wired Inserts (DCWI). Also, it is found that Nusselt number and the pressure drop in the DCWI are respectively (44.2% -100%) and (101.27% - 172.8%) greater than those of the flat duct with WI. The improvement in Nusselt number for flat duct with WI is found to be (1.4 – 2) times the values for flat duct with no WI. The results demonstrated that DCWI provides enhancements efficiency value that is higher than those obtained from other types of ducts. The developed MSW ducts have added to local knowledge a better understanding of the compound heat transfer enhancement.